Santri Melek AI Rekonstruksi Mindset Digital Menuju Prestasi Belajar Unggul di MA Al-Ahliyah - Solihah Bagus; Taufik Luthfi; Mar’ahtul Azizah Bela Norma Kholis (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
The rapid development of digital technology, particularly Artificial Intelligence (AI), has significantly transformed the field of education. However, the reality in Islamic schools and pesantren shows that many students remain passive users of technology, utilizing it mainly for entertainment rather than as a tool for learning. Through the program “Santri Al-Ahliyah Embracing AI: Reconstructing the Digital Mindset Towards Excellent Learning Achievement”, this community service project aims to foster a constructive digital mindset among students of MA Al-Ahliyah, enabling them to use AI wisely, productively, and ethically to enhance their academic performance. The program was implemented in three stages: socialization, training, and mentoring. The results indicate an improvement in students’ understanding of AI concepts, greater awareness of the importance of digital literacy, and increased motivation to integrate technology into learning activities while maintaining Islamic values. The satisfaction survey further revealed that most participants perceived the program as highly beneficial, giving high appreciation to the facilitators in terms of mastery of the material, systematic delivery, provision of relevant examples, and encouragement of active participation. This program demonstrates that reconstructing the digital mindset in pesantren can effectively strengthen students’ capacity to face the challenges of the Industrial Revolution 4.0 and Society 5.0.Abstrak Perkembangan teknologi digital, khususnya Artificial Intelligence (AI), membawa perubahan besar dalam dunia pendidikan. Namun, realitas di madrasah dan pesantren menunjukkan bahwa santri masih cenderung menjadi pengguna pasif teknologi, lebih banyak memanfaatkannya untuk hiburan daripada pembelajaran. Melalui program “Santri Al-Ahliyah Melek AI: Rekonstruksi Mindset Digital Menuju Prestasi Belajar yang Unggul”, kegiatan pengabdian ini bertujuan membangun mindset digital santri MA Al-Ahliyah agar bijak, produktif, dan etis dalam memanfaatkan AI untuk mendukung prestasi belajar. Metode kegiatan dilakukan melalui tiga tahap: sosialisasi, pelatihan, dan pendampingan. Hasil pelaksanaan menunjukkan peningkatan pemahaman santri mengenai konsep AI, kesadaran akan pentingnya literasi digital, serta munculnya motivasi baru untuk mengintegrasikan teknologi dalam kegiatan belajar tanpa meninggalkan nilai-nilai keislaman. Hasil survei kepuasan juga menggambarkan bahwa mayoritas peserta menilai kegiatan sangat bermanfaat, dengan apresiasi tinggi terhadap fasilitator dalam penguasaan materi, penyampaian yang sistematis, pemberian contoh konkret, serta mendorong partisipasi aktif. Program ini membuktikan bahwa rekonstruksi mindset digital di pesantren dapat memperkuat kapasitas santri menghadapi era Revolusi Industri 4.0 dan Society 5.0.